2022
DOI: 10.1111/1756-185x.14374
|View full text |Cite
|
Sign up to set email alerts
|

Clinical variables, including novel joint index, associated with future patient‐physician discordance in global assessment of rheumatoid arthritis (RA) disease activity based on a large RA database in Japan

Abstract: Background: Discordance between patient global assessment (PGA) and physician global assessment (PhGA) of rheumatoid arthritis (RA) disease activity is mainly determined by pain and functional disabilities. This study aimed to investigate the shift in PGA-PhGA discordance and the variables associated with future positive discordance (PGA > PhGA) based on the NinJa database in Japan. Methods:We examined 7557 adults with RA registered in both NinJa 2014 and 2018, with a discordance cutoff of 3 on a 10-cm scale. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
(112 reference statements)
0
3
0
Order By: Relevance
“…In our data, there was an association of anxiety and depression with index visit discordance in unadjusted analyses, though this was attenuated in multivariable analyses. Although a few previous observational studies have evaluated how patient-clinician discordance evolves over time (2,7,10,11), to our knowledge only two examined factors associated with persistent discordance. In the aforementioned singlecenter study among US Hispanic patients, patients with persistent positive discordance over 2 years were more likely to have fibromyalgia and irreversible articular damage (10).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our data, there was an association of anxiety and depression with index visit discordance in unadjusted analyses, though this was attenuated in multivariable analyses. Although a few previous observational studies have evaluated how patient-clinician discordance evolves over time (2,7,10,11), to our knowledge only two examined factors associated with persistent discordance. In the aforementioned singlecenter study among US Hispanic patients, patients with persistent positive discordance over 2 years were more likely to have fibromyalgia and irreversible articular damage (10).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, persistent discordance was associated with greater activity impairment and loss of employment and/or work productivity. In a study of Japanese patients with RA, persistent discordance was associated with pain and modified health assessment questionnaire (MHAQ) scores ( 11 ). A longitudinal study that did not assess persistent discordance also found that discordance was associated with progressive joint destruction and functional impairment ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation